Use of Ethylene Polyterephatalate (PET) as aggregate in concrete block (Research, Society and Development, 2022)
The Ethylene Polyterephatalate (PET) is a type of polyester that is part of human daily life, having many advantages in relation to weight, practicality in transport and storage, being used to manufacture packaging in order to store and conserve food, grains, beverages, medicines, material. prime for the manufacture of fabrics, among others. However, like most polluting materials, when PET is incorrectly disposed of on streets, landfills and even dumps, it causes major negative impacts on the environment. In view of the current scenario focused on sustainability issues, a civil construction area positively seeks innovations and ecologically correct alternatives, sustainable materials ​​with a lower population rate in its projects and with a guarantee of an opportunity to build a sustainable planet essential for the well-being of current and future generations. Thus, analyzing the current scenario, the idea arose to study the possibility of using PET bottles crushed in the same granulometry as sand, as a substitute for cement in the manufacture of sustainable blocks, in the hope of obtaining good resistance, thus reducing the irregular disposal of this material in the environment. Compressive strength tests were performed and confirmed that the best proposal was composed of 27% PET and 73% sand had the best strength, although relatively low when compared to other percentages of the same materials. There was low agglomeration between the polymer and the sand, generating empty spaces that influenced the resistance.